From Eastern Prophets to Syrian Yankees: Tracing the First Generations of Arab American Writers - Dostálová, Zuzana (American & British Studies Annual, 2024)
The article discusses the first generations of Arab American writers with the aim to identify the narrative strategies they employed. The focus is primarily on the representatives of the Mahjar movement (Khalil Gibran, Ameen Rihani) along with observations of the roles that they adopted through their writing pursuits (the role of the prophet/man of letters). Furthermore, the text examines selected literary works of Salom Rizk, Vance Bourjaily, and William Peter Blatty as the representatives of the second generation of Arab American authors who desired to be identified as Americans. The article argues that in the first two generations of Arab American writers, the authors’ storytelling techniques are generally rooted either in self-orientalizing narrative strategies as represented by the character of an “Eastern prophet” or by an assimilating strategy epitomized by the character of a “Syrian Yankee.”